Lexical changes in the 1643 and 1671 editions of the Book of Sirach by Georgius Mancelius - Kazakėnaitė, Ernesta (Baltistica, 2023)
This study is about lexical changes in the reprint editions of the Book of Sirach. The first edition of Das Hauß=Ʒucht=vnd Lehrbuch Jeſu Syrachs, translated into Latvian by Georgius Mancelius and published in Riga in 1631 by Gerhard Schroeder, is briefly discussed at the beginning of the article. However, the focus is on the lexical changes made in the next two editions. Thus, the second part of the article deals with the changes made by Mancelius himself to the vocabulary of the translation in the second edition (1643), while the third part deals with the changes found in the edition of 1671. The aim was to find out whether and how the editing of the translation differed in terms of vocabulary and what exactly was no longer considered relevant. This question arises from the knowledge that the translator and editor of the first reprint edition was the same Mancelius, but that the reprint edition of 1671 of the book appeared after his death and was worked on by others (one or other of the Riga pastors).
Keywords: 17th century Latvian texts; Georgius Mancelius; the Book of Sirach; editing